Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Joseph W. Jordan, December 18, 1988 - Jordan, Joseph W.et al (1988)
Iowa Christmas bird counts of species found at Lake Red Rock contributed by Joseph W. Jordan, December 18, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed